UPAYA PENINGKATAN HASIL BELAJAR ROUNDERS MELALUI MODIFIKASI PERMAINAN YANG DISEDERHANAKAN PADA SISWA KELAS V SD NEGERI 04 SIMPUR KECAMATAN BELIK KABUPATEN PEMALANG TAHUN PELAJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to improve the quality of teaching physical education primarily through modification of thematerial rounders disederhanankan game . The instrument used for data collection in this study is theobservation sheet , questionnaire , and student test performance . Analysis of the data used in this study is adescriptive analysis . The results showed that the implementation of learning rounders game with gamemodifications can be simplified ynag make their lessons more active , enthusiastic students participating inlearning and seem happy to carry out a given task motion so that the teacher and the student movement skillmastery rounders game increased so that the values obtained by students also increased the percentage ofstudents from initial conditions that reached a minimum completeness criteria as much as 46.4 % or 13students out of the total number of students by 28 students , the percentage of students first cycle of action thatreached completeness Minimum Criteria to 71.4 % or as many as 20 students and 82 % or as many as 23students in the second cycle of action . According to the results of this study concluded that learning roundersthe game yag simplified modification can increase the active participation and student learning outcomes in theform of the value of the game rounders